The effects of dipping pretreatments on air-drying rates of the seedless grapes - Doymaz, I; Pala, M (ELSEVIER SCI LTD, 2002)
Turkey has a significant potential for fruit and vegetable production. Grape is an economically important item for Turkey's export. However, problems encountered during drying of grapes have not yet been resolved. The effects of different dipping solutions on hot air drying of grapes were studied. Seedless grapes pretreated with alkaline emulsion of ethyl oleate (AEEO) resulted in comparatively good quality raisins. Grapes dipped into ethyl oleate solution prior to drying showed shorter drying times than those untreated, or pretreated with potassium carbonate solution. Colour analysis of grapes showed that the best results are obtained in grapes which were pretreated with an AEEO and dried with air at 60 degreesC. The drying rates of grapes were modeled by the Page and Exponential equations. The model results agreed with experimental results. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: grape; hot-air drying; pretreatment solution; mathematical models; KINETICS; RAISINS; SLICES; SUN; Engineering; Food Science & Technology